Preparation of Silver Nanostructures from Bicontinuous Microemulsions. (30th May 2012) - Pedroza-Toscano, M. A.; Rabelero-Velasco, M.; Díaz de León, R.; Saade, H.; López, R. G.; Mendizábal, E.; Puig, J. E.
Abstract : Precipitation of silver nanoparticles at 70°C was carried out by dosing a 1.3 M sodium borohydride aqueous solution over bicontinuous microemulsions formed with a mixture of sodium bis(2-ethylhexyl) sulfosuccinate (AOT) and sodium dodecylsulfate (SDS) as surfactants, a 0.5 M silver nitrate aqueous solution, and toluene. Weight ratios of 2.5/1 and 3/1 AOT/SDS were used in the precipitation reactions. Silver nanoparticles were characterized by transmission electronic microscopy, X-ray diffraction, and atomic absorption spectroscopy. A mixture of isolated spheroidal nanoparticles ( ≈ 15 wt.%) with an average diameter around 10 nm and wormlike structures ( ≈ 85 wt.%) with an average length close to 480 nm and an average diameter ca. 40 nm was obtained, regardless of the AOT/SDS ratio. Higher yields were obtained compared with those reported when reverse microemulsions were employed. Formation of wormlike structures was ascribed to one-dimensional aggregation of crystal and particles within the channels of bicontinuous microemulsions, which performed as templates.